G44 A Prospective Questionnaire Assessment of Knowledge and Application of Estimated Glomerular Filtration Rates Amongst Paediatric Trainees. (4th June 2013) - Hay, EL; Newnham, A; O'Brien, C
Abstract : Aims: To determine awareness of estimated glomerular filtration rates (eGFR) and its application in prescribing and managing paediatric patients. Methods: This was a cross-sectional, prospective, questionnaire based study. The questionnaires were distributed at the regional deanery teaching for Paediatric trainees at levels ST1–8 in Autumn 2012. Results: 40 questionnaires were completed, with a 50% response rate. Trainee groups were categorised as junior trainees, ST1–3 (n = 17), senior trainees, ST4–8 (n = 16) or trainees specifically with renal experience (n = 7). Almost a third of the total number of participants had never performed an eGFR, three-quarters of whom were junior trainees. Not surprisingly therefore, one-third of junior trainees had never adjusted medication in consideration of renal impairment. Likewise, three-quarters of trainees were unable to suggest a formula for calculating an eGFR. Of significance, from the 25% who were able to give a formula, 30% wrote it incorrectly. In the clinical scenarios 80% correctly identified an abnormal creatinine but less than half realised the need to dose adjust acyclovir. In the second case 75% appropriately indicated the use of Gentamycin in renal impairment but there was no clear consensus on the dosing regime and when levels should be checked. Only 20% were aware of the 24-hour dosing schedule with almost half opting to look it up or discuss with the renal team. Overall those with more training (ST4–8) or with renal experience (ST1–8) were more knowledgeable. Conclusions: There is significant room for improvement in the knowledge and appropriate use of eGFR amongst Paediatric trainees, particularly at the junior level. An increasing awareness of these simple tests would improve prescribing practise; potentially preventing the inappropriate use of nephrotoxic drugs in those with renal impairment or conversely denying a patient gentamicin when it is the most suitable antibiotic and safe if used appropriately. We hope to establish simple regional guidelines through the local nephrology network, develop practical prescribing modules to improve prescribing in renal impairment and consequently improve clinical decision-making and reduce the burden on tertiary nephrology services.